THE MIRROR OF PRAXIS: A NARRATIVE LITERATURE REVIEW OF TEACHER REFLECTION FOR PROFESSIONAL GROWTH - Hasibuan, Kalayo; Khair, Nadiatul; Rahmi Dalimunthe, Nazhifah; Gusnaeni, Reni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In the rapidly evolving educational landscape of the twenty-first century, teachers are expected to continuously adapt their pedagogical practices to meet the changing needs of learners, curricula, and technological advancements. Reflective practice has emerged as one of the most influential approaches for supporting teachers’ professional growth and lifelong learning. This narrative literature review synthesizes findings from 45 studies published between 1995 and 2026 to examine the role of teacher reflection in fostering professional development. Drawing upon literature related to reflective practice, teacher professional development, teacher identity, professional agency, collaborative reflection, and technology-assisted reflection, this review identifies five major themes. The findings reveal that reflective practice functions as a fundamental mechanism for improving pedagogical knowledge, instructional decision-making, professional identity formation, and teacher agency. The review further highlights the increasing importance of collaborative reflection through Professional Learning Communities (PLCs) and the emerging role of artificial intelligence (AI) and digital technologies in supporting reflective learning. Despite these benefits, several challenges remain, including time constraints, institutional pressures, and the tendency for reflection to remain at descriptive rather than critical levels. The review argues that meaningful professional growth occurs when teachers engage in critical reflection that challenges assumptions, informs action, and promotes continuous learning. The study concludes that reflection should be viewed not merely as a professional activity but as a transformative process that supports sustainable teacher development and educational improvement.